A CONCEPTUAL REVIEW ON HINGULA (CINNABAR- HgS) - *Patel Asma; M.Gopi Krishna; J.Shashidhar (International Journal of Ayurveda and Pharma Research, 2019)
Rasa Shastra the unique branch of Ayurveda deals in detail about pharmaceutical and therapeutic uses of various metals, minerals and marine drugs. Hingula (cinnabar) is one among several important drugs in Ayurveda which is used as single remedy or as an ingredient in various herbo-mineral preparations. By most of the ayurvediya Rasa Shastra classics, it is grouped under Sadharana Rasa Varga. Hingula is the prime source of mercury. Chemically it consists of mercury (86%) and Sulphur (13.5%), with molecular formula HgS, called as red sulphide of Mercury. About 20 books of Rasa Shastra are reviewed by the author in an attempt to provide the detailed description about Hingula like its occurrence, synonyms, classification, pharmacological properties, Ashuddha Hingula Dosha, its antidote, Shodhana, Marana, therapeutic dose, therapeutic indications, Sattvapatana, artificial methods of cinnabar preparation, methods of extraction of mercury from Hingula and various specific formulations mentioned in classics. Purified Hingula is useful in the treatment of all types of eye diseases (Netra Roga), it mitigates all the three vitiated Doshas. It is best remedy for the disorders of liver, pancreas, rheumatoid arthritis (Amavata), diabetes mellitus (Prameha) fever, spermatorrhoea and leprosy, skin diseases (Kushtha). It is useful in Parada Jarana procedure (increasing therapeutic potency of mercury). The mercury extracted from cinnabar (Hingulottha Parada) is equivalent to Ashtsamskarita Parada which is used in the preparations. It also possesses all the properties of Gandhaka Jaarita Parada (digestion of sulphur in mercury). It is used in the incineration procedures of gold, silver etc metals.